Governing Landscapes for Ecosystem Services: A Participatory Land-Use Scenario Development in the Northwest Montane Region of Vietnam - Do, T.H.; Vu, T.P.; Catacutan, D. (Springer, 2021)
Land-use planning is an important policy instrument for governing landscapes to achieve multifunctionality in rural areas. This paper presents a case study conducted in Na Nhan commune in the northwest montane region of Vietnam to assess land-use strategies toward multiple ecosystem services, through integrated land-use planning. The assessment employed the Land-Use Planning for Multiple Ecosystem Services (LUMENS) framework and a number of methods and tools, including land-use mapping, GIS-based land-use change analysis, survey questionnaire, rapid carbon-stock appraisal for different land uses, qualitative ecosystem services assessment, and a backcasting technique. Our findings suggest that a lack of participation and acknowledgement of customary land-use practices inhibit successful implementation of current land-use planning and relevant policies such as payment for forest environmental services and the nationally determined contributions. The study also confirmed the contributions of forests and the land-use sector in achieving national emission reduction targets, especially when local stakeholders are involved early in the planning process. Other findings with important policy implications are: (i) tree-based land uses such as agroforestry are key to securing multiple ecosystem services and are highly relevant to local stakeholders, yet their potentials were not made explicit in current debates at the local level; (ii) local stakeholders are highly aware of the co-benefits of ecosystem services to climate-change mitigation and this should be considered in nationally determined contributions; and (iii) an approach for integrated, participatory land-use planning can help catalyze stakeholder engagement, and hence improve governance in rural landscapes.